2015
DOI: 10.1039/c4gc02457e
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-free synthesis of a Sn-BEA catalyst by dry gel conversion

Abstract: Sn containing molecular sieves with BEA topology (Sn-BEA) are active Lewis catalysts for a large variety of redox reactions. However, the synthesis of Sn-BEA often requires the use of toxic chemicals (e.g. hydrofluoric acid). In this study, we demonstrated that an active Sn-BEA catalyst can be directly synthesized in a non-fluoride medium via a dry gel conversion method with the aid of seed crystals. It was shown that seeding of zeolite BEA crystals can facilitate crystal growth and lead to BEA topology with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 48 publications
2
94
0
Order By: Relevance
“…For these comparisons to be meaningful, it is critical to always establish a benchmark in studies comparing multiple materials. For example, the activity of HT Sn-Beta for glucose isomerization in water (82,88,90) featuring a TOF = 100-120 (mol glucose) (mol Sn) −1 h −1 at 368-383 K when using an initial concentration of (mol glucose) (mol Sn) −1 = 100 has been reproduced by several research groups; hence, it can be used as a reliable benchmark. As more alternative synthesis techniques are developed, the consistent use of benchmark materials should be complemented by including comparisons on a metal content or acid site count basis rather than total catalyst mass, so that more relevant conclusions can be drawn about the nature of the active centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these comparisons to be meaningful, it is critical to always establish a benchmark in studies comparing multiple materials. For example, the activity of HT Sn-Beta for glucose isomerization in water (82,88,90) featuring a TOF = 100-120 (mol glucose) (mol Sn) −1 h −1 at 368-383 K when using an initial concentration of (mol glucose) (mol Sn) −1 = 100 has been reproduced by several research groups; hence, it can be used as a reliable benchmark. As more alternative synthesis techniques are developed, the consistent use of benchmark materials should be complemented by including comparisons on a metal content or acid site count basis rather than total catalyst mass, so that more relevant conclusions can be drawn about the nature of the active centers.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the type of metal salt used as a precursor in hydrothermal syntheses heavily influences the framework content and catalytic activity of the final product (79,80). Recently, many groups have reported dry-gel or postsynthetic methods for metal incorporation in zeolite Beta (21,81,82). These methods can often incorporate a higher metal content into the zeolite framework compared with the hydrothermal method, leading to higher yields normalized by total catalyst mass for certain reactions, but usually have lower TOFs when normalized by metal content at loadings above 3-5% (83-85).…”
Section: Effects Of Synthesis Techniquesmentioning
confidence: 99%
“…Significant efforts have been made for shortening the crystallization time by seeded growth methods [22][23][24] . An interesting method was proposed by Chang et al 23 , who demonstrated that Sn-BEA can be synthesized in non-fluoride media via dry gel conversion using a seeded growth procedure. An interesting method was proposed by Chang et al 23 , who demonstrated that Sn-BEA can be synthesized in non-fluoride media via dry gel conversion using a seeded growth procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the absorption band at approximately 260 nm that is attributed to octahedral Sn 4+ spaces is not observed for the calcined Sn-S MC . On the other hand, the band at 240–250 nm is still in debate, however, penta-coordinated Sn species [30,31], extra-framework Sn species [17], and small tin oxide particles [30,32] have been assigned to the peaks at around 240–250 nm. These results strongly support the idea that Sn 4+ ions were introduced into the Sn-MFI framework as tetrahedrally coordinated states.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance peaks of CD 3 CN on the ‘closed Sn’ and the ‘open Sn’ sites are at 2309 cm −1 and 2317 cm −1 , respectively. This result suggests that Sn-S MC and Sn-S HT have the ‘closed’ Sn(OSi) 4 structure [31,32]. Furthermore, all samples show no absorbance at 2317 cm −1 due to the ‘open’ Sn site.…”
Section: Resultsmentioning
confidence: 99%